A Concept Model Toward Coral Reefs Literacy : Case Study on Primary Schools Students - Manapa, Esther Sanda; Rustaman, Nuryani (Journal of Indonesian Coral Reefs, 2011)
One of the competencies in to develope the knowledge and to build up public awarness on the importancy of the sea human life, is the sustainability and management of coasltal and marine ecosystems, ie.: the mangrove, seagrass, and coral reefs ecosystems. From those three ecosystems, the coral reef is the most dominant as the habitat of various fish species. Because of that, the coral reefs deserves a more empathy and love feeling to raise the appreciation of the community on the Coral reef ecosystems conservation. These appreciation and awareness will be most effective to be introduced since theearly ages. This process is necessary to establish to corall reef literacy. this study was aimed to examine thi concepts of coral reefs ecosystem to be offered in the prymary school.The selected concepts has to be considered through its acceptability, subtantive supports, and other influencing factors, leading to priorotizing of workable concepts variables. As a technical approach for decision making, descriptive, quantitative and interpretative analysis were aplied accordingly, througs three stage of research: (1) The oceanic concepts of Indonesian childresn among inland and coastal community form 8 to 12 years old (case study)., (2) The profil of coral reefs world through the eyes of Indonesia elementary s prepective (case study: 4th, 5 th, and 6th graders)., (3) Concepts model of coral reefs knowledge for marine science learning program in the primary school. I general this research reveal that the development of coral reefs literacy based on competency for 4th, 5th and 6th graders needs to be implemented and could be divided into three phases: phase I, Understanding; Phase II, Application and Phase III, Analysis.